Smart Cluster Communication Integration and Architecture - Babu Natha, Rajesh; Sreenivasa Ravi, K (International Journal of Engineering and Technology, 2018)
In the present day modern world, most of the people are making use of the technology in many ways which made man feasible to complete his tasks at very low time. In this aspect of digitalization, almost all the levels of the society is able to use the services of modern technology like wireless communication, Information Storage and transfer. In this aspect, an emerging medium for smart solution is LPWAN. It uses LoRa communication protocol for Information Interchange. This paper deals with the architecture of smart clusters of cities and solutions to some problems like Public safety, Pollution, Traffic management, Parking Solutions.Â